Council Tax Policies and Territorial Governance: Analysis and Outlook of a Difficult Relationship - Rusci, Simone (TeMA - Journal of Land Use, Mobility and Environment, 2015)
In recent years, the dependency of local public finance from various forms of taxation related to urban development and real estate has become increasingly evident in Italy. Nevertheless, to date no organic relationship seems to have been established between fiscal policies, on the one hand, and urban planning, on the other. This article examines the ties linking the two areas, focusing on different types of taxes and discussing the aspects that have come to influence the area of planning, with special regard to territorial competition, urban equalization, building rights and land consumption mitigation measures.